ASSOCIATION OF NEUTROPHIL LYMPHOCYTE RATIO WITH SEVERITY AND OUTCOME OF ACUTE ISCHEMIC STROKE PATIENTS - CHANDE, ABHISHEK; BAWANKULE, SHILPA; KUMAR, SUNIL (International Journal of Psychosocial Rehabilitation, 2020)
The cumulative incidence of stroke ranged from 105 to 152/100,000 persons per year, and the crude prevalence of stroke ranged from 44.29 to 559/100,000 persons in different parts of the country during the past decade. Stroke is the second leading cause of death worldwide and mostly presents acutely. Among the strokes, ischemic stroke accounts for approximately 80% to 85% of the cases, and is characterized by the disruption of cerebral blood. Acute ischemic stroke is an inflammatory event where the ischemic tissues release chemokines and cytokines, and recruit peripheral circulating leukocytes. This will be a Cross-sectional study. Patients admitted with cerebrovascular event in medicine intensive care unit and medicine wards at the Acharya Vinobha Bhave Rural Hospital. 100 patients with acute ischemic stroke admitted in the department of medicine. The outcome of the research will be discussed after the correlation between NLR and prognosis of AIS is obtained. Baseline neutrophil numbers may be related to tissue damage severity, reinfarct risk, and poor neurologic outcome.